The thermal performance study of biomass field-erected water tube boilers using analytical model / Sivabalan Tanapala - Sivabalan , Tanapala (2013)
Renewable Energy is one of the major contributors in fulfilling the world’s energy demand. Biomass is one of the renewable energy sources which are currently being exploited by the community. Palm oil industries use the waste from processed palm fruits, shell and empty fruit bunch as fuel to generate steam in order to cook the fresh fruits and generate power for the whole plant. Tropical climate in Malaysia provides the best platform for the palm trees to grow and maintain Malaysia’s ranking as second largest palm oil producer in the world. Stoker firing water tube boilers are used widely in the mills as it is the best method that converts the chemical energy in the fuel through combustion into mechanical energy which runs the turbine to generate electricity. A comprehensive review have been done through this paper on the existing design, fuel, heat transfer, heat losses and CFD studies of biomass boiler. The heat transfer and heat losses in the boiler due to biomass combustion have been analysed and studied thoroughly in the literatures. The present design of boiler used in the tropical countries is based on the empirical data from western countries due to lack of tropics data’s. Higher temperature, humidity and wind velocity of tropical climate impact on the boiler and its component efficiency were studied. Other than that the effect on fuel demand and the heat transfer in the components were also studied. An actual running unit in Casanare, Colombia which is in tropical zone were selected and simulated for the study. The cost impact and the payback period were determined for the best and worst climate condition that happens in the tropics.